The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/0261927x14534656
|View full text |Cite
|
Sign up to set email alerts
|

Information Manipulation Theory 2

Abstract: Information Manipulation Theory 2 (IMT2) is a propositional theory of deceptive discourse production that conceptually frames deception as involving the covert manipulation of information along multiple dimensions and as a contextual problem-solving activity driven by the desire for quick, efficient, and viable communicative solutions. IMT2 is rooted in linguistics, cognitive neuroscience, speech production, and artificial intelligence. Synthesizing these literatures, IMT2 posits a central premise with regard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
87
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 57 publications
1
87
0
Order By: Relevance
“…Moreover, not a single study in our main meta-analysis revealed a significant reversed RT lie effect (i.e., significantly longer RT for truth telling compared to lying, with the 95% CI not including zero, see Table 1) 8 . This pattern of results is interesting in light of the current debate about whether lying is always more effortful than truth telling or whether -and if so under which circumstances -truth telling may be more effortful than lying (Levine, 2014;McCornack et al, 2014;Verschuere & Shalvi, 2014). Our findings revealed a surprising stability of the cognitive cost of deception, even in some of the situations that have been proposed to modulate or reverse this cost (e.g., practiced deception, relevant information, and motivated liars; De Paulo et al, 2003;McCornack et al, 2014;Walczyk et al, 2014).…”
Section: Is Lying Always More Demanding Than Truth Telling?mentioning
confidence: 78%
See 3 more Smart Citations
“…Moreover, not a single study in our main meta-analysis revealed a significant reversed RT lie effect (i.e., significantly longer RT for truth telling compared to lying, with the 95% CI not including zero, see Table 1) 8 . This pattern of results is interesting in light of the current debate about whether lying is always more effortful than truth telling or whether -and if so under which circumstances -truth telling may be more effortful than lying (Levine, 2014;McCornack et al, 2014;Verschuere & Shalvi, 2014). Our findings revealed a surprising stability of the cognitive cost of deception, even in some of the situations that have been proposed to modulate or reverse this cost (e.g., practiced deception, relevant information, and motivated liars; De Paulo et al, 2003;McCornack et al, 2014;Walczyk et al, 2014).…”
Section: Is Lying Always More Demanding Than Truth Telling?mentioning
confidence: 78%
“…Finally, liars have to monitor their own behavior and that of their interaction partners in order to control behaviors that may be interpreted as lying. In sum, the cognitive view holds that deception is typically more cognitively demanding than truth telling (Ellwanger, Rosenfeld, Sweet, & Bhatt, 1996;Johnson, Barnhardt, & Zhu, 2004;Spence et al, 2004;Vrij, 2008;Zuckerman, DePaulo, & Rosenthal, 1981; for an opposing view see e.g., McCornack, Morrison, Paik, Wisner, & Zhu, 2014; for boundary conditions see e.g., Walczyk, Harris, Duck, & Mulay, 2014).…”
Section: The Cognitive Approach To Deceptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, some researchers believe that lying is prevalent in everyday life because lying is less cognitively effortful than truth-telling in many situations (McCornack et al, 2014). …”
Section: Introductionmentioning
confidence: 99%